Selective IgG4 deficiency and autoimmune cytopenias - Maria Loutsou; Nikolaos Giannakoulas; Emmanouel Ηatzipantelis; Helen Pergantou; Athina Dettoraki; Vasiliki Antari; Aikaterini Michalopoulou; George Vassilopoulos; Styliani Sarrou; Vasiliki Kalaitzidou; Christos Hadjichristodoulou; Fani Kalala; et al. (Exploration of Immunology)
Aim: Autoimmune cytopenias are disorders driven by immune-mediated destruction of hematopoietic cells. Recent studies have linked these conditions to inborn errors of immunity (IEI), particularly in patients with recurrent and/or chronic forms. Common variable immunodeficiency (CVID) is the most common IEI in humans, and autoimmune cytopenias represent the most prevalent autoimmune manifestations of the disease. TNFRSF13B/TACI alterations are the most common genetic defects in CVID patients. The aim of this study was to investigate both the incidence of hypogammaglobulinemia—including immunoglobulin subclass deficiencies—in patients with autoimmune cytopenias, as well as possible correlations with common TNFRSF13B/TACI defects in selective patients. Methods: A cohort of 123 patients (110 adults and 13 children, male/female: 58/65, median age at diagnosis: 50.0 years, range: 1.5–87.0) with autoimmune cytopenias [113 with autoimmune thrombocytopenia (AIT), 8 with autoimmune hemolytic anemia (AHA), and 2 with Evans syndrome] were enrolled in the study. The main immunoglobulin types (IgG, IgM, and IgA) were measured in all patients, while serum for the estimation of IgG subclass levels was available in 84 patients. Genetic analysis of TNFRSF13B/TACI was performed by PCR and Sanger sequencing. Results: Although no deficiency of main immunoglobulin types was detected in any patient, 8 of 84 patients (9.5%) displayed selective IgG4 deficiency (sIgG4D). Among them, three suffered from acute/newly diagnosed AIT, three from chronic AIT, and two from AHA. Interestingly, two patients with sIgG4D exhibited a family history of IEI. Furthermore, one patient (12.5%) carried a pathogenic missense mutation (c.542C>A, p.A181E, rs72553883) in a heterozygous state, while the remaining patients carried only common polymorphisms. Conclusions: IgG4 could be considered a useful biomarker in patients with autoimmune cytopenias, while further studies may elucidate its precise role in disease pathogenesis and prognosis.